PENDAMPINGAN PEMBUATAN PANGAN FUNGSIONAL TEH KASKARA KEPADA POKTAN SUKATANI DESA SUKAWANGI BOGOR - Nining Nining; Yeni Yeni; Fith Khaira Nursal; Anisa Amalia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sukatani is a farmer group in Sukawangi Village, Sukamakmur District, Bogor Regency, that requires assistance processing coffee peels. So far, coffee post-harvest technology has only focused on the fruit, while the peel, known as cascara, has been limited to animal feed or even thrown away. Cascara contains antioxidants, phenolic compounds and caffeine, which can potentially be used as a functional food for tea materials. Tea consumption is considered part of a balanced diet, enhancing the antioxidant and overall health status. Cascara processing can be an additional income for farmers, so applying appropriate technology to cascara is necessary. This service activity aims to design tea production using cascara and to diversify coffee products. Cascara is made into dried simplicia and powdered, then packaged in tea bags. This activity is carried out with the direct training tutoring method so that the response or target feedback can be obtained spontaneously and quickly. Activities evaluation is carried out to measure knowledge and achievement success. Statistically, there was an increase in the average score from the pretest (40.36) to the posttest (52.21) with a Sig. (2-tailed) 0.003 (< 0.05) using paired t-test. Thus, the evaluation results show a significant increase in knowledge of the activity target.